What are drugs? - Super, Gretchen, 1955- (Frederick, Md. : Twenty-First Century Books, 1990)
Examines, in simple text and illustrations, what drugs are, what they can do to your body, and the problems of drug addiction.
Includes index.
Keywords: Drug abuse -- Juvenile literature; Drugs -- Juvenile literature; Drugs; Drug abuse